The Health of Lisp-Stat - Pedro M. Valero-Mora; Frederic Udina (Journal of Statistical Software, 2004)
Lisp-Stat seems to be quite inert nowadays. However, there is no widespread agreement about what actually killed it, or even whether it has really passed away or not. Here we present the papers included in this special issue of the Journal of Statistical Software about it. Some of the included papers are about what Lisp-Stat was able to do in the past, other give testimony of the current state of health of Lisp-Stat, and other analyze whether there is any chance of its eventual recovery.